Assessing the Manufacturing Characteristics (Technological and Financial) as Determinants of Productivity of the Manufacturing Industry in Nigeria: Cross Sectional Survey Approach. - Isa, Usman Bature; Musa, Lawal Batsari (NIU Journal of Humanities, 2018)
The paper assesses the Manufacturing Characteristics (Technological and Financial) as Determinants of Productivity of the Manufacturing Industry in Nigeria. The study adopted a cross sectional data obtained from four (4) manufacturing industries which were in operation by the year 2016 production season. Data was analyzed using STATA Version 13 (Nonparametric and Parametric Statistics). The result indicated that technology, equipment accessibility, finance as well as capital base were good determinants of Productivity in manufacturing industry in Nigeria. It is recommended that new technology should be put in place, avenue for capital investment should be provided and efficient management should take charge.